Characterization of Natural Organic Matter in Conventional Water Treatment Processes and Evaluation of THM Formation with Chlorine - Kadir Özdemır (The Scientific World Journal)
This study investigates the fractions of natural organic matter (NOM) and trihalomethane (THM) formation after chlorination in samples of raw water and the outputs from ozonation, coagulation-flocculation, and conventional filtration treatment units. All the water samples are passed through various ultrafiltration (UF) membranes. UF membranes with different molecular size ranges based on apparent molecular weight (AMW), such as 1000, 3000, 10,000, and 30,000 Daltons (Da), are commonly used. The NOM fraction with AMW < 1000 Da (1 K) is the dominant fraction within all the fractionated water samples. Its maximum percentage is 85.86% after the filtration process and the minimum percentage is 65.01% in raw water samples. The total THM (TTHM) yield coefficients range from 22.5 to 42 μg-TTHM/mg-DOC in all fractionated samples, which is related to their specific ultraviolet Absorbance (SUVA) levels. As the molecular weight of the fractions decreased, the TTHM yield coefficients increased. The NOM fractions with AMW values less than 1 K had lower SUVA values (<3 L/mg·m) for all treatment stages and also they had higher yield of TTHM per unit of DOC. The NOM fraction with AMW < 1 K for chlorinated raw water samples has the highest yield coefficient (42 μg-TTHM/mg-DOC).